Hydrilla Management in Florida Lakes - Stacia A. Hetrick; Ken A. Langeland (EDIS, 2012)
Hydrilla is the most aggressive invasive plant in Florida waters. It can provide some benefits to fish and wildlife at low levels of coverage, but it also can have major detrimental impacts to water uses, causing substantial economic and environmental hardships. This 6-page fact sheet was written by Stacia A. Hetrick and Ken A. Langeland, and published by the UF Department of Agronomy, March 2012.